The Impact Of Using Chatgpt On University Students’ Ability To Write Lecture Assignment - Fadil Akbar; Naufal Ahmad Rijalul Alam (At-Tarbiyat, 2024)
ChatGPT (Generative Pre-Training Transformer) is one of the media that is often used and accessed by students to get information and facilitate students in learning. In addition, the use of ChatGPT helps students in writing and facilitates students in the writing process. This study aims to find the impact of using ChatGPT on students' writing skills. This study used a quantitative approach by involving the use of questionnaires as one of the data collection techniques. The questionnaire used to collect data in the form of responses and views of students who were intended as respondents in this study was the impact of using ChatGPT on students' writing skills. In research stated that the use of ChatGPT has an impact on students' writing skills, so ChatGPT can be one of the tools or media that can help students in writing and become a medium that helps students to improve writing skills. However, the use of ChatGPT in writing also has a negative impact behind it, which can make students spoiled and lazy to think when writing, this is because ChatGPT technology is able to understand human language so that it can meet what students want.